Overclaimed Refunds, Undeclared Sales, and Invoice Mills: Nature and Extent of Noncompliance in a Value-Added Tax - Mazhar Waseem (Center for Economic Studies and ifo Institute (CESifo), 2020)
I leverage a Pakistani tax reform that cuts the tax rate on the supply chains of five major industries of the country from 15% to 0% to cast light on the extent of, and mechanisms driving, VAT noncompliance in a representative emerging economy. I find that firms overclaim refunds by 22% and underreport domestic B2C sales by 43.5%. Together, this implies an evasion rate of 77% in the treated industries and 38% in the population. I explore the role of three mechanisms (1) the destination principle, (2) the last-mile problem, and (3) invoice mills in driving this noncompliance.
Keywords: H25; H26; H32; 330; VAT; tax evasion; firm behavior